Plato Under Review: What Is Going Wrong in Academic Philosophical Writing - Giacomo Pezzano (Humanities)
This paper addresses the problem of stylistic pluralism in philosophical writing, arguing that its progressive narrowing to the form of the paper is not just an esthetic issue but can also have negative effects on the development of academic research itself. The contribution is divided into two parts (Sections 1–3 and 4–5). In the first part, after introducing the problem and outlining the main features of the philosophus academicus’s writing, two main forms of criticism of “paper-centrism” in academic philosophy are discussed—one more “anti-academic” and the other more “intra-academic”. In light of these criticisms, the issue of the relationship between form and content in philosophical writing is analyzed with particular respect to the problem of the sense of truth, arguing that style communicates philosophical values beyond content. In the second part, this thesis is illustrated by examining, as a case study, the specific sense of truth conveyed in Plato’s dialogues—first through a literary analysis of Platonic writing, and then through a thought experiment inspired by media theory. Finally, the ethical and epistemic concerns raised by the growing “mono-stylism” of philosophical writing are brought together into a unified framework, by proposing a preliminary sketch of an ethics of philosophical research and pointing to some possible examples of alternative research practices.